Analisis Pengaruh Faktor Internal Dan Eksternal Terhadap Profitabilitas Pt Bank Bca Syariah, Tbk - Valzsa, Teuku Zadhe; Rahmi, Mira (Islamic Economics and Business Review, 2023)
Profitability as a benchmark in assessing profit becomes very important in checking whether a company has run its business efficiently, a bank uses ROA or Return on Assets as a measure of bank profitability. PT Bank BCA Syariah, Tbk, which is one of the Islamic banks in Indonesia with stable ROA growth, can be used as a benchmark for the growth of Islamic banking in Indonesia. This study aims to determine internal and external factors that can affect the profitability of PT Bank BCA Syariah, Tbk for the period 2012 to 2021. Internal factors use the Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) and Operational costs and operating income (BOPO). Then on external factors using the BI Rate and GDP, using multiple linear regression analysis techniques. Results of this study shows that FDR and BOPO has an effect on ROA, meanwhile NPF, BI Rate and GDP has no effect. This research is expected to be useful for the development of Islamic banks in Indonesia, by knowing the factors that has an effect on profitability of Islamic banks.